THE HONEY BEES OF INDONESIA (HYMENOPTERA: APIDAE) - Michael S Engel (Treubia, 2012)
A brief account is provided for the native and introduced species of honey bees (Apini: Apis L.) occurring across Indonesia. Keys to the tribes of corbiculate bees and the species of the genus Apis are provided to aid melittologists and apiculturists working in the country.